NAVIGATING BARRIERS: MIGRATION OF LITHUANIAN SINGLE MOTHERS AND WELFARE IN GERMANY, NORWAY AND THE UK - Greta Skubiejūtė (PEOPLE: International Journal of Social Sciences, 2025)
This presentation examines the migration experiences of Lithuanian single mothers, driven by inadequate support in their home country, leading them to seek better economic opportunities in Germany, Norway, and the UK. The research objective is to identify the barriers and opportunities single mothers face due to varying family policies in these countries. The methodology includes policy analysis and semi-structured interviews with single mothers, applying life-course theory to analyse how family policies shape their experiences over time. While these countries offer improved socio-economic conditions, challenges persist, particularly in balancing family and work responsibilities. Norway’s comprehensive family policies promote gender equality through better defamilialisation and decommodification, whereas Germany and the UK offer moderate support. The research emphasises the need for gender-responsive policies that ensure economic independence and social recognition for single mothers, enhancing both their well-being and participation in society. Future research could compare the situation of single mothers with two-parent families across EU countries to identify how gendered policies are. Research findings could be applied to policy recommendations aimed at improving gender equality and socio-economic outcomes for single mothers.